(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluation of the results of endoscopic tympanoplasty in children at Nghe An Obstetrics and Pediatrics Hospital. Methods: Cross-sectional study, descriptive study with clinical intervention from June 2020 to June 2022. Result: Preoperative functional symptoms: 96.7% of patients complained of otorrhea, 80% of patients experienced hearing loss, 10% of patients suffered from otalgia and headache. The most common TM perforation is pantympanic perforation. The postoperative PTA average was 23.72±8.51, which was significantly lower than the mean preoperative hearing level of 35.35±9.52 db. Postoperative functional symptoms improved markedly. More details, otorrhea has decreased dramatically from 96.7% to 0%, hearing loss has felt from 93.3% to 73%, and tinnitus has declined nearly 50% (from 80% to 33%). The percentage of successful tympanic membrane perforation closure has reached 96.7% while the proportion of failure has been only 3.3%.